(untitled) (Journal of actual problems of jurisprudence, 2016)
This article considers questions of a freedom of speech and legal status of the personality and their interrelation. At the same time investigated legal status of personality. An author in this article investigates rights and individual freedoms according to categories. An author on the basis of analysis examines freedom of speech.